Public Relations Strategies for Sustaining Donor Support for the Beringin Bhakti Foundation - Aninditto Rivally Sudarisman; Siti Khumayah; Aghnia Dian Lestari (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2026)
Trust is the one thing that cannot be faked and for a foundation that relies on donors' good intentions to retain their commitment, it's not just philosophy, it's business. The Beringin Bhakti Cirebon Foundation is in this very situation: an institution of charity whose mission thrives or dies with the donors' belief in its continuing existence. This research examines how public relations actually underpins this trust for the Foundation. Transparency, clear communication of what the foundation is doing without embellishment, Honesty, which at the Foundation, seemed less a stated belief and more an unquestioned habit, and the feeling of an emotional connection, the genuine warmth that institutions often claim to deliver, were recurrent in the data. The research was carried out using a qualitative methodology through observation, interview, and documentation with the Chairperson, PR personnel and long-time donors of the Foundation. The data showed a relatively uncomplicated finding: when individuals feel heard, seen, and cared for, they stick around. Transparency leads to donors' security. Honesty fosters respect. And emotion to commitment.